Pelatihan Bahasa Inggris “Tenses” Bagi Siswa Sekolah Minggu HKBP Getsemane Medan Labuhan - Pasaribu, Arsen Nahum; Sembiring, Rony Arahta; Sondang Manik; Tiara K Pasaribu; Leriana Marbun; Melissa Sidauruk (LPPM Universitas HKBP Nommensen, 2024)
Mastery of English is a must for everyone around the world. Likewise in Indonesia, mastering English will provide great benefits for future studies and careers. However, students still experience obstacles in learning and practicing English either in the school environment or in the community because English is a foreign language for the Indonesian people, which is not used as an official or everyday language. Therefore, the PKM activities of the Faculty of Languages ​​and Arts, HKBP Nommensen University try to provide solutions to students and the community to improve their ability to master English. By focusing on English 'tenses' training for Sunday school students at the HKBP Getsemane church, Martubung Medan. The training participants were 20 elementary and middle school students who were Sunday school children and church teenagers. The training lasted for two weeks with three meetings each week, starting from 16-28 October 2023. After the training was carried out, the results of the training in the form of trainee test scores showed significant progress in the trainee's ability to understand and practice English tenses, both written and verbal. From the observations it was also found that the training participants were very enthusiastic and interested in learning English using the methods used in class.